Magnetic Resonance Imaging of the Axial Skeleton in Patients With Spondyloarthritis: Distribution Pattern of Inflammatory and Structural Lesions. Issue 10 (28th August 2017) - Hoffstetter, Patrick; Al Suwaidi, Mohammed H; Joist, Alexander; Benditz, Achim; Fleck, Martin; Stroszczynski, Christian; Dornia, Christian
Purpose: Spondyloarthritis is a chronic inflammatory disorder of the musculoskeletal system driven by systemic enthesitis and typically involving the axial skeleton, ie, the spine and the sacroiliac joints. The purpose of this study was to assess the distribution pattern of inflammatory and structural magnetic resonance imaging (MRI) findings in spondyloarthritis. Methods: Retrospective study of 193 patients with axial spondyloarthritis who received MRI of the spine and the sacroiliac joints. We quantitatively assessed inflammatory and structural lesions using established MRI-based scoring methods. The significance of the differences between gender, HLA-B27 status, and spine and sacroiliac involvement was determined. Results: In total, 174 patients (90.2%) showed a sacroiliac involvement and 120 patients (62.2%) a combined involvement of the sacroiliac joints and the spine. An isolated sacroiliac involvement was found in 54 patients (28.0%) and an isolated spine involvement in 19 patients (9.8%). The sacroiliac joint was significantly more involved in men than in women ( P < .01), and men had significantly higher scores for structural lesions ( P < .001). The subgroup of HLA-B27–positive patients showed a significantly higher percentage of sacroiliac involvement compared with HLA-B27–negative patients ( P < .05). Conclusions: Spondyloarthritis is a systemic disorder predominantly involving the sacroiliac joints. However, the entire axial skeleton may be affected. In particular, HLA-B27–negative women show atypical manifestations without sacroiliac involvement. Magnetic resonance imaging in spondyloarthritis should cover the entire axial skeleton, ie, sacroiliac joints and the spine to meet the pathophysiology of this disorder and capture the true extent of inflammatory and structural lesions.